The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.24198/jkp.v2n2.7
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Keluarga terhadap Skizofrenia

Abstract: AbstrakKeluarga yang memiliki anggota keluarga dengan skizofrenia mengalami isolasi sosial karena stigma yang melekat pada penderita. Oleh karena itu, penderita skizofrenia sering kali disembunyikan dan dikucilkan agar tidak diketahui oleh masyarakat. Padahal persepsi keluarga yang positif sangat dibutuhkan dalam perawatan pasien skizofrenia. Tujuan dari penelitian ini yaitu untuk mengetahui persepsi keluarga terhadap skizofrenia. Penelitian ini menggunakan metode deskriptif kuantitatif. Sampel pada penelitian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…Some families still conceal the presence of their schizophrenic family members from social surroundings. The study conducted by Suryani, Komariah, and Karlin (2014) confirmed this and reported that 4 out of 6 family members admitted feeling confused, disliked, and ashamed being part of a family with schizophrenic family members. These feelings made them unable to provide proper care for a schizophrenic family member and later relapse.…”
Section: Introductionmentioning
confidence: 56%
“…Some families still conceal the presence of their schizophrenic family members from social surroundings. The study conducted by Suryani, Komariah, and Karlin (2014) confirmed this and reported that 4 out of 6 family members admitted feeling confused, disliked, and ashamed being part of a family with schizophrenic family members. These feelings made them unable to provide proper care for a schizophrenic family member and later relapse.…”
Section: Introductionmentioning
confidence: 56%
“…In this study, the study subject was recruited the majority of males with an average age of 37,25 ± 12,714, with the majority employment status not working and the most unmarried like the results of this study following the existing theory that the majority of Schizophrenia are men, unmarried and yet to work. This phenomenon occurs because this mental disorder causes the sufferer to struggle to obtain a job and to run a marriage either as a result of his illness or a negative "stigma" obtained due to mental illness He suffered (2,9,10).…”
Section: Discussionmentioning
confidence: 99%